Cultivating Lecturer Professionalism in Islamic Higher Education: A Phenomenological Exploration of Disciplinary Alignment, Digital Adaptation, and Ethical Engagement - Muhammad Iqbal; Saiful Akhyar Lubis; Masganti Sitorus (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Professionalism among Guidance and Counseling lecturers plays a vital role in improving the quality of higher education and fulfilling the Tri Dharma of Higher Education—teaching, research, and community service. While teacher professionalism has been widely discussed, limited attention has been given to its development within Islamic higher education, where academic competence is closely intertwined with moral and social values. This study examines the readiness and professional development strategies of Guidance and Counseling lecturers at Institut Agama Islam Negeri (IAIN) Langsa in Aceh, Indonesia. Using a qualitative phenomenological approach, the research explores lecturers’ lived experiences in shaping professional identity and practice. Data were collected through observation, in-depth interviews, and document analysis involving ten purposively selected informants, including institutional leaders, lecturers, staff, and students. Data were analyzed through stages of collection, condensation, display, and conclusion drawing. The findings reveal that lecturer professionalism is constructed through three interconnected dimensions: disciplinary alignment in teaching, adaptive integration of digital technology, and sustained engagement in research and community service grounded in counseling ethics. The study concludes that professionalism in Islamic higher education extends beyond technical competence to include ethical commitment and contextual responsiveness, highlighting the need for integrated institutional support for sustainable professional development.